Pemberdayaan Masyarakat Melalui Pelatihan Pembuatan Abon Jambu Mete (Anacardium occidentalle) di Desa Tegal Maja Kabupaten Lombok Utara - Sucika Armiani; Siti Rabiatul Fajri; Masiah Masiah; Laras Firdaus; Herdiyana Fitriani; Nurfitria Komalasari (Nuras : Jurnal Pengabdian Kepada Masyarakat, 2022)
Tegal Maja Village is one of the villages in North Lombok Regency whose main commodity is cashew nuts. Cashew fruit consists of a true fruit in the form of a spindle or seed, while the pseudo-flesh is often known as a fruit that contains a lot of water. Cashew nuts are an important commodity while the fruit is considered to have no economic value because of its astringent taste, so it is often used as animal feed or even thrown away. The purpose of this community service activity is to increase the knowledge and skills of the people of Tegal Maja Village, North Lombok Regency in processing cashew fruit into shredded fruit, as well as supporting village programs in processing local potential into UMKM products. The implementation of activities carried out for 3 weeks includes initial observations, preparation of activity programs, discussions on determining activity schedules, and implementation of core activities. The core activities include the opening, socialization, practice of making floss, and product delivery. The success of this activity was measured by the increased knowledge and skills of participants in processing cashew fruit flesh into floss. The partner's response to this activity was very good, marked by the enthusiasm of the participants, namely 100% attendance, arriving on time until the activity ended. This community service activity ended with the delivery of products to the Head of Tegal Maja Village, North Lombok Regency.